A protocol for developing, disseminating, and implementing a core outcome set for pre-eclampsia - Duffy, J; van 't Hooft, J; Gale, C; Brown, M; Grobman, W; Fitzpatrick, R; Karumanchi, S; Lucas, N; Magee, L; Mol, B; Stark, M; Thangaratinam, S; et al. (Elsevier, 2016)
Background: Pre-eclampsia is a serious complication of pregnancy and contributes to maternal and offspring mortality and morbidity. Randomised controlled trials evaluating therapeutic interventions for pre-eclampsia have reported many different outcomes and outcome measures. Such variation contributes to an inability to compare, contrast, and combine individual studies, limiting the usefulness of research to inform clinical practice. The development and use of a core outcome set would help to address these issues ensuring outcomes important to all stakeholders, including patients, will be collected and reported in a standardised fashion. Methods: An international steering group including healthcare professionals, researchers, and patients, has been formed to guide the development of this core outcome set. Potential outcomes will be identified through a comprehensive literature review and semi-structured interviews with patients. Potential core outcomes will be entered into an international, multi-perspective online Delphi survey. All key stakeholders, including healthcare professionals, researchers, and patients will be invited to participate. The modified Delphi method encourages whole and stakeholder group convergence towards consensus 'core' outcomes. Once core outcomes have been agreed upon it is important to determine how they should be measured. The truth, discrimination, and feasibility assessment framework will assess the quality of potential outcome measures. High quality outcome measures will be associated with core outcomes. Mechanisms exist to disseminate and implement the resulting core outcome set within an international context. Discussion: Embedding the core outcome set within future clinical trials, systematic reviews, and clinical practice guidelines could make a profound contribution to advancing the usefulness of research to inform clinical practice, enhance patient care, and improve maternal and offspring outcomes. The infrastructure created by developing a core outcome set for pre-eclampsia could be leveraged in other settings, for example selecting research priorities and clinical practice guideline development. Prospective registration: [1] Core Outcome Measures in Effectiveness Trials (COMET) registration number: 588.[2] International Prospective Register of Systematic Reviews (PROSPERO) registration number: CRD42015015529.